2019
DOI: 10.1093/hmg/ddz161
|View full text |Cite
|
Sign up to set email alerts
|

A trans-ancestral meta-analysis of genome-wide association studies reveals loci associated with childhood obesity

Abstract: Although hundreds of genome-wide association studies-implicated loci have been reported for adult obesity-related traits, less is known about the genetics specific for early-onset obesity and with only a few studies conducted in non-European populations to date. Searching for additional genetic variants associated with childhood obesity, we performed a trans-ancestral meta-analysis of 30 studies consisting of up to 13 005 cases (≥95th percentile of body mass index (BMI) achieved 2–18 years old) and 15 599 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 24 publications
2
70
0
Order By: Relevance
“…Many studies suggest that the polymorphism of this gene is associated with obesity and the development of type 2 diabetes (14). A multicenter study of more than 13,000 children aged 2-18 with BMI above 95 percentile years confirmed the occurrence of this gene polymorphism in obese children (15). The variant of gene FAIM2-rs7138803 is associated with BMI z-scores in children over 6 years (16).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Many studies suggest that the polymorphism of this gene is associated with obesity and the development of type 2 diabetes (14). A multicenter study of more than 13,000 children aged 2-18 with BMI above 95 percentile years confirmed the occurrence of this gene polymorphism in obese children (15). The variant of gene FAIM2-rs7138803 is associated with BMI z-scores in children over 6 years (16).…”
Section: Discussionmentioning
confidence: 94%
“…It can play a role in cerebellum development. The polymorphism of the molecular coding gene is associated with giant obesity and diabetes mellitus type 2 and increases the risk of cardiovascular diseases (14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, for three loci ( EBF1 , NCOA1 and SEC16B) , nearly all alleles associated with decreased birth weight were associated with higher CBMI/COB risk (Table S4 – S5 ). Furthermore, we evaluated our findings using the European-ancestry summary statistics in a recent childhood obesity GWAS 46 . Out of the 342 SNPs in our study found to be associated with both birthweight and childhood obesity, 98.5% reached > 95% posterior probability when we used this validation childhood obesity GWAS (Table S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, a reduction in the oxidative capacity of brown adipocytes results in impaired thermogenesis, and has been linked to diet-induced obesity (33) . In this context, it’s important to note that microdeletion and SNPs in METTL15 gene are highly associated with obesity (16, 17) . Therefore, we speculate that if altered METTL15 activity impacst obesity onset, it’s likely to be due to the ability of METTL5 to regulate mitochondrial functions by methylating 12S mt-rRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the microdeletion region always encompasses a METTL-famlily protein METTL15. More recently, a trans-ancestral meta-analysis of genome-wide association studies uncovered a completely novel single nucleotide polymorphism (SNP) (rs10835310) at METTL15 associated with childhood obesity, ( 17 ), further implicating the involvement of METTL15 in this human syndrome, although the underlying molecular mechanisms for these associations is still unclear.…”
Section: Introductionmentioning
confidence: 99%